1992
DOI: 10.1002/dev.420250102
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and postweaning excretion of puberty‐influencing chemosignals in house mice

Abstract: Pre- and postweaning excretion of urinary chemosignals that influence puberty in female house mice were tested. The dependent variable used to assess the effectiveness of urine samples collected from donor mice was the age of first vaginal estrus in young female mice. Preweaning excretion of the puberty-delaying chemosignal by females was affected by litter sex composition; this effect interacted with the age of the young donor females. In litters of all females, the substance occurred from about the age of 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In mice, puberty-delaying urinary chemosignals can be released by very young, preweaned female mice, although their pubertydelaying effects may not be as robust as those of urine from adult female mice (Drickamer, 1992). It may not be coincidental that the presence of sisters in the current study (especially older sisters) was associated with delayed menarche.…”
Section: Discussionmentioning
confidence: 61%
“…In mice, puberty-delaying urinary chemosignals can be released by very young, preweaned female mice, although their pubertydelaying effects may not be as robust as those of urine from adult female mice (Drickamer, 1992). It may not be coincidental that the presence of sisters in the current study (especially older sisters) was associated with delayed menarche.…”
Section: Discussionmentioning
confidence: 61%
“…In this view, it should be noted that brain dopaminergic and adrenergic pathways are reported to playa major role in the neuroendocrine control of reproduction, and that cocaine administration has been shown to interact negatively with puberty-related processes in mice (see Chen & Vandenbergh, 1993). Taken together, these reports indirectely suggest that interference by peri pubertal sexual segregation with gonadal hormones and their metabolites on pubertal development (Drickamer 1992;Lupo di Prisco et aI., 1978;Vandenbergh, 1989) of modulatory monoaminergic systems in the CNS should be considered.…”
Section: Discussionmentioning
confidence: 95%
“…Prepubertal sexual segregation altered the function of monoaminergic eNS systems mediating the drug actiona neural substrate considered an important participant in an organism's responding to environmental challenge (Laviola et aI., 1994 )-as revealed by the restriction to mixed-sex reared mice of the modulatory effects of cocaine (see, e.g., Figure 3, lower panel on the right). This specific manipulation of rearing environment has also been related to changes in gonadal hormone regulation (Drickamer, 1992;Lupo di Prisco, Lucarini, & Dessi'-Fulgheri, 1978), and Savageau and Beatty (1981) reported that gonadectomy of male rats also affected the behavioral response to an amphetamine challenge (see . In this view, it should be noted that brain dopaminergic and adrenergic pathways are reported to playa major role in the neuroendocrine control of reproduction, and that cocaine administration has been shown to interact negatively with puberty-related processes in mice (see Chen & Vandenbergh, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, preweaning female mice reared in all-female litters are reported to be delayed in attaining first estrus in relation to females reared in litters with 1 or more males. As outlined by Drickamer (1992), there must be some internal events, as yet unmeasured, that are altered by a litter sex composition that involves no males. The hormonal and neurological effects of starting development in an all-female litter must be explored further.…”
Section: Discussionmentioning
confidence: 99%